Analisis Penerapan Job Order Costing Method Terhadap Harga Pokok Produksi Untuk Meningkatkan Akurasi Harga Jual Produk Pada Maju Jaya Aluminium Kecamatan Cina Kabupaten Bone - Martinah Martinah; Muctar Nuhung (Institut Agama Islam Negeri (IAIN) Bone, 2018)
This study aims to compare the cost of the 2M CA type of storefront production that has been applied in Forward Jaya Aluminum by calculating the production cost principle using the job order costing method. Data is collected through observation, interviews, and documentation. Furthermore, the data is analyzed using qualitative methods. While the calculation method used in this study is the method of job order costing or the cost of the order. The results of the study found that the calculation of the cost of production of type 2 M CA storefront was IDR 1,300,000 with a set profit rate of 19.6% with a selling price of IDR 1,550,000, while the calculation using the job order costing method was equal to Rp 1,329,217 with a selling price of Rp 1,589,744 with a profit rate of 19.6%. Based on the results of his analysis, the difference in the calculation of cost of goods manufactured is due to the fact that Maju Jaya Aluminum does not identify in detail the elements of the cost of production, so the cost of production calculated by Maju Jaya Aluminum is lower than using the job order costing method. We recommend that Maju Jaya Aluminum correct the calculation of cost of goods manufactured according to the job order costing method by calculating and identifying raw material costs, direct labor costs, and factory head costs so that the specified selling price can be accurate and increase.